God Attachment, Mother Attachment, and Father Attachment in Early and Middle Adolescence - Sim, Tick N. (Journal of religion and health, 2011)
The present study examined the interplay of attachment to God, attachment to mother, and attachment to father with respect to adjustment (hope, self-esteem, depression) for 130 early and 106 middle adolescents in Singapore. Results showed that the parental attachments were generally linked (in expected directions) to adjustment. God attachment, however, had unique results. At the bivariate level, God attachment was only linked to early adolescents' self-esteem. When considered together with parental attachments (including interactions), God attachment did not emerge as the key moderator in attachment interactions and yielded some unexpected results (e.g., being positively linked to depression). These results are discussed viz-a-viz the secure base and safe haven functions that God and parental attachments may play during adolescence.